Autophagy-related protein LC3β and its association with clinical-pathological characteristics, mismatch repair proteins and survival in colorectal carcinoma - Gakinya, Samuel; Nzioka, Ancent K.; Mugo, Alex G.; Onyuma, Timothy; Ogutu, James (Frontiers in Medicine, 2025)
IntroductionAutophagy is a metabolic process that serves to maintain cellular homeostasis as well as enable the cell to adapt to metabolic stress. In malignant cells, autophagy has been associated with drug resistance, metastasis and poor outcome. Colorectal carcinoma is a leading cause of cancer morbidity and mortality worldwide. The management and outcome are dependent on the tumor clinical and pathological characteristics. Autophagy is a potential therapeutic target as well as prognostic biomarker given its role in cancer pathogenesis. This study aimed at evaluating the autophagy status of colorectal carcinomas for tumors diagnosed at the Aga Khan University Hospital, Nairobi and establish its association with clinical-pathological characteristics including age, tumor location, tumor grade, tumor pathological stage, tumor nodal stage, tumor budding, tumor-infiltrating lymphocytes (TILs), Mismatch repair protein status (MMR), HER2 status and patient survival.MethodsThe study assessed the autophagy status of 114 colorectal carcinoma cases using immunohistochemistry for autophagy related protein LC3β. The clinical-pathological characteristics were determined by examining the medical records and evaluation of hematoxylin and eosin-stained slides. HER2 and MMR status were evaluated using immunohistochemistry. The treatment outcome was determined from the patient's records by checking for date of last visit or death.Results and discussionThe mean age of patients in our study was 58years. There were more males 61.8% (n = 70) than females 38.6% (n = 44). Most of the patients had high pathological tumor stage of pT3 and pT4. Majority of the tumors showed intermediate tumor budding and weak tumor-infiltrating lymphocytes. The mismatch repair deficiency and HER2 overexpression were found in 14.9% (n = 17) and 2.6% (n = 3) of the cases respectively. LC3β was overexpressed in 36% (n = 41) of the cases and was significantly more common in females (p = 0.013). The LC3β status showed no significant association with age, tumor location, tumor grade, tumor stage, nodal stage, tumor budding, tumor-infiltrating lymphocytes, MMR status, HER2 status or patient survival. Future prospective studies are recommended to further explore the utility of autophagy as a prognostic and predictive biomarker.